Polymorphism in carbohydrate self-assembly at surfaces: STM imaging and theoretical modelling of trehalose on Cu(100). Issue 61 (4th November 2019) - Abb, Sabine; Tarrat, Nathalie; Cortés, Juan; Andriyevsky, Bohdan; Harnau, Ludger; Schön, J. Christian; Rauschenbach, Stephan; Kern, Klaus
Abstract : We rationalize the experimentally observed variety of trehalose assemblies on Cu(100) by modeling based on STM images and global optimization. Abstract : Saccharides, also commonly known as carbohydrates, are ubiquitous biomolecules, but little is known about their interaction with surfaces. Soft-landing electrospray ion beam deposition in conjunction with high-resolution imaging by scanning tunneling microscopy now provides access to the molecular details of the surface assembly of this important class of bio-molecules. Among carbohydrates, the disaccharide trehalose is outstanding as it enables strong anhydrobiotic effects in biosystems. This ability is closely related to the observed polymorphism. In this work, we explore the self-assembly of trehalose on the Cu(100) surface. Molecular imaging reveals the details of the assembly properties in this reduced symmetry environment. Already at room temperature, we observe a variety of self-assembled motifs, in contrast to other disaccharides like e.g. sucrose. Using a multistage modeling approach, we rationalize the conformation of trehalose on the copper surface as well as the intermolecular interactions and the self-assembly behavior.